Product Pricing Decision Support System with the Simple Additive Weighting Method - Nadya Alinda; Ilmawati (Universitas Putra Indonesia YPTK Padang, 2023)
The development of information systems today has caused quite significant changes in the pattern of decision making within a company. The development of this information system has also made changes from various groups who act as information seekers to always obtain the most appropriate and accurate information that can be used in the process of updating information. Furniture data management at the Kabun Raya Furniture store is still done manually and product pricing is done based on furniture data records. Doing product pricing based on manual management can cause manipulation of product data which makes product pricing irrelevant. To overcome these problems, we need a system that provides convenience in storing and processing product data in the store. The method used in this research is field research, library research, and laboratory research. The tool used for design is UML (Unified Modeling Language). By implementing a decision support system using the PHP Programming Language and MySQL Database, it makes it easy for leaders to determine product prices.